Surveillance and molecular characterization of banana viruses associated with Musa germplasm in Malawi - Johnny Isaac Gregorio Masangwa; Nuria Fontdevila Pareta; Philemon Moses; Eva Hřibová; Jaroslav Doležel; Isaac Fandika; Sebastien Massart (PLoS ONE, 2026)
Malawi has diverse local banana germplasms that are preferred by its population. However, the epidemics of banana bunchy top disease (BBTD), caused by the banana bunchy top virus (BBTV) is wiping out the preferred germplasms and limiting their cultivation. A survey was conducted to characterize banana germplasm and evaluate the presence, incidence and prevalence of banana viruses. PCR products from infected germplasm were sequenced and aligned for each detected virus to construct a phylogenetic tree. BBTV, banana mild mosaic virus (BanMMV) and six banana streak virus (BSV) species were detected in Malawi. Malawi’s BBTV isolates belonged to the Pacific Indian Ocean group, and BanMMV isolates clustered to three sub-branches. The six BSV species detected in Malawi belonged to clade 1. Among the genetic groups of Musa , the characterized banana germplasms belonged to AA, AAA, AAB, and ABB groups with some germplasms being unique compared to those already genotyped. The ABB group was dominant in Malawi and was significantly more often infected by BSV species (possibly originating from endogenous viral sequences), while BBTV and BanMMV infected the AAA and AAB group more frequently, respectively. The primary source of banana planting materials was banana propagule exchange among relatives which posed a higher risk of spreading virus diseases. The survey underlined the importance of establishing a banana seed industry and implementing policies that promote farmers’ access to virus-tested planting materials, ultimately helping to prevent future virus epidemics.